2020
DOI: 10.3389/fpls.2020.585674
|View full text |Cite
|
Sign up to set email alerts
|

Weak Tradeoff and Strong Segmentation Among Plant Hydraulic Traits During Seasonal Variation in Four Woody Species

Abstract: Plants may maintain long-term xylem function via efficiency-safety tradeoff and segmentation. Most studies focus on the growing season and community level. We studied species with different efficiency-safety tradeoff strategies, Quercus acutissima, Robinia pseudoacacia, Vitex negundo var. heterophylla, and Rhus typhina, to determine the seasonality of this mechanism. We separated their branches into perennial shoots and terminal twigs and monitored their midday water potential (Ψmd), relative water content (RW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Notably, some researches indicated that the “air-injection” method may be prone to artifacts if the maximum length of the xylem vessels is not considered when preparing the samples for conducting the measurements (Ennajeh et al, 2011 ). However, this research was based on 4-month-old saplings, it is impossible to have a long conduit like a tree, according to the shape of our HVC ( Figure 2 ) and previous researches (Zhu et al, 2018 ; Li et al, 2019 , 2020 ; Liu et al, 2020 ), we convince that the 30-cm-long segments had no open vessels, so that the “air-injection” method did not cause experimental artifacts in this research. Moreover, the “air-injection” method can accurately control the stem water potential, and it can improve the precision of the HVC (Sergent et al, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Notably, some researches indicated that the “air-injection” method may be prone to artifacts if the maximum length of the xylem vessels is not considered when preparing the samples for conducting the measurements (Ennajeh et al, 2011 ). However, this research was based on 4-month-old saplings, it is impossible to have a long conduit like a tree, according to the shape of our HVC ( Figure 2 ) and previous researches (Zhu et al, 2018 ; Li et al, 2019 , 2020 ; Liu et al, 2020 ), we convince that the 30-cm-long segments had no open vessels, so that the “air-injection” method did not cause experimental artifacts in this research. Moreover, the “air-injection” method can accurately control the stem water potential, and it can improve the precision of the HVC (Sergent et al, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
“…Notably, some researches indicated that the "air-injection" method may be prone to artifacts if the maximum length of the xylem vessels is not considered when preparing the samples for conducting the measurements (Ennajeh et al, 2011). However, this research was based on 4-month-old saplings, it is impossible to have a long conduit like a tree, according to the shape of our HVC (Figure 2) and previous researches (Zhu et al, 2018;Li et al, 2019Liu et al, 2020), we convince that the 30-cm-long segments had no open vessels, so that the "air-FIGURE 4 | Differences among: CK, D 3 , D 8 (A); D 12 U, R 2 U to REU (C); D 12 L, R 2 L to REL (E) for the stem water potential (Ψ ). The loss of conductivity (LC) differences among CK, D 3 , D 8 (B); D 12 U, R 2 U to REU (D); and D 12 L, R 2 L to REL (F).…”
Section: Drought Did Not Change the Water Transport Efficiencymentioning
confidence: 83%
See 1 more Smart Citation
“…Subsequently, the samples were transported promptly to the laboratory with the crowns covered with black plastic bags. All leaves and bark were removed, and each segment of R. pseudoacacia was 30 cm long, while that of Q. acutissima was 20 cm long, to ensure there would never be open vessels ( Liu et al, 2020 ). The segments were connected to a hydraulic conductivity measurement system that contained degassed, filtered 20.0 mmol L –1 KCl solution.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon has aggravated the existing spatiotemporal uneven water distribution in the warm temperate zone ( Luan et al, 2011 ; Corlett, 2016 ), leading to the alternation of drought and rewatering. Severe drought may lead to plant hydraulic failure, which has been invoked as the most direct and critical mechanism causing tree dieback and forest mortality ( Martinez-Vilalta and Pinol, 2002 ; Nardini et al, 2013 ; O’Grady et al, 2013 ; Liu et al, 2020 ). After drought, the pace of recovery differs among physiological processes; leaf water potential typically recovers within few days even few hours upon rewatering, while leaf gas exchange-related variables lag ( Ruehr et al, 2019 ), leading to plant growth traits slow recovery ( Li et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%